The Cannabinoid 2 Receptor as a Potential Therapeutic Target for Sepsis - Richard Kasten, Kevin; Tschop, Johannes; Hans Tschop, Matthias; Curtis Caldwell, Charles (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2010)
The sepsis syndrome represents an improper immune response to pathogens and is associated with an unacceptably high rate of mortality. Although supportive care is of benefit to the septic patient, there are no viable therapeutics available that target the immune system suitable for the whole septic population. Recently, using a physiologically relevant murine mouse model, the cannabiniod 2 receptor has been shown to play a critical role in the host response to sepsis. Here, the structure, expression, signaling, and function of the CB2 receptor on leukocytes will be reviewed. Further, the effects mediated by the CB2 receptor during sepsis will be reviewed. Altogether, alterations in inflammation and the host response during sepsis by the CB2 receptor support its use as a possible therapeutic agent.
Keywords: T cells